Macrophages Down-Regulate Gene Expression of Intervertebral Disc Degenerative Markers Under a Pro-inflammatory Microenvironment - Silva, Ana J.; Ferreira, Joana R.; Cunha, Carla; Corte-Real, João V.; Bessa-Gonçalves, Mafalda; Barbosa, Mario A.; Santos, Susana G.; Gonçalves, Raquel M. (Frontiers in Immunology, 2019)
Low back pain is a highly prevalent clinical problem and intervertebral disc (IVD) degeneration is now accepted as the major pathophysiological mechanism responsible for this condition. Accumulating evidence suggests that inflammation plays a crucial role in the progression of human IVD degeneration, with macrophages being pointed as the key immune cell players in this process since their infiltration in degenerated IVD samples has been extensively demonstrated. Since they are highly plastic, macrophages can play different roles depending on the microenvironmental cues. The study of inflammation associated with IVD degeneration has been somehow neglected and one of the reasons is related with lack of adequate models. To overcome this, we established and characterized a new model of IVD organ culture under pro-inflammatory conditions to further dissect the role of macrophages in IVD associated immune response. For that, human monocyte-derived macrophages were co-cultured either with bovine caudal IVD punches in the presence of the pro-inflammatory cytokine IL-1β, or IVD-conditioned medium (CM), to investigate how IVD-produced factors influence macrophage phenotype. After 72h, metabolic activity, gene expression and cytokine profile of macrophages and IVD cells were measured. Our results show that macrophages and IVDs remain metabolically active in the presence of IL-1β-stimulated IVDs, significantly upregulate CCR7 gene expression and increase production of IL-6. When treating macrophages with IL-1β-IVD-CM, CCR7 upregulation follows the same trend, while for IL-6 an opposite effect was observed. On the other hand, macrophages interfere with IVD ECM remodelling, decreasing MMP3 expression and downregulating aggrecan and collagen II gene expression in the presence of IL-1β. Overall, the co-culture model established in this study can be considered a suitable approach to address the cellular and molecular pathways that regulate macrophage-IVD crosstalk, suggesting that degenerated IVD tissue tends to polarize human macrophages towards a more pro-inflammatory profile, which seems to aggravate IVD degeneration. This model could be used to improve the knowledge of the mechanisms that link IVD degeneration and the immune response.